The Influence of Surface Morphology of Buffer Layer on the Critical Current Density in YBCO Coated Conductors - Jie Xiong; Yudong Xia; Fei Zhang; Yan Xue; Kai Hu; Xiaohui Zhao; Bowan Tao (Advances in Condensed Matter Physics)
1 μm-thick YBa2Cu3O7-δ (YBCO) films were grown on the Y2O3/yttria stabilized zirconia (YSZ)/CeO2 buffer layers with different surface morphologies using direct-current sputtering. The critical current density (Jc) value of YBCO was 1.1 MA/cm2 when the root mean square surface roughness (Rrms) of the buffer layer was 2.5 nm. As the Rrms of the buffer layer increased to 15 nm, the Jc decreased to 0.3 MA/cm2. X-ray diffraction and scanning electron microscopy showed the strong relevance of the evolution of the structure and surface morphologies of YBCO films with the buffer layer of different Rrms. A model was proposed to explain the influence of surface morphology on the superconducting properties of YBCO films.